DEVELOPMENT OF NUMERACY LITERACY INSTRUMENTS IN THE LOCAL SOCIO-CULTURAL CONTEXT OF SERANG FOR HIGH SCHOOL STUDENTS - Umroh, Umroh; Nindiasari, Hepsi (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2024)
To enhance students' numeracy literacy skills, it is essential to develop an instrument that measures these abilities accurately. This research aims to develop a numeracy literacy instrument tailored to the local socio-cultural context of Serang for high school students. The instrument development method employed an RD (Research and Development) approach using the Wilson model as well as the Oriondo and Antonio model. The subjects of this study were 20 eleventh-grade students from SMAN 8 Kota Serang, selected through purposive sampling techniques. Utilizing both qualitative and quantitative data analysis techniques, the study produced five items that were valid, reliable, and practical. Validity testing showed a score of 89.89% from three experts, and a Cronbach’s Alpha value of 0.75, indicating reliability. The instrument's practicality, as derived from student responses, was rated at 88.4%, categorized as highly practical. Therefore, the numeracy literacy test instrument developed in the local socio-cultural context of Serang is suitable for high school students. The findings suggest that this instrument can effectively assess numeracy literacy skills within this specific cultural context, providing a valuable tool for educators.